A father for Bella - Weatherholt, Jill (Love inspired., 2018)
When single mom Faith Brennan discovers the Virginia inn she grew up in is for sale, she's determined to make a bid. Even if that means going head-to-head with handsome real estate broker Joshua Carlson. But competing with Joshua would be a lot easier if Faith's young daughter wasn't growing so attached to him...and if Faith could stop picturing running the inn with Joshua by her side.